High-throughput sequencing of small RNAs from pollen and silk and characterization of miRNAs as candidate factors involved in pollen-silk interactions in maize. - Xiao Ming Li; Ya Lin Sang; Xiang Yu Zhao; Xian Sheng Zhang (PLoS ONE)
In angiosperms, successful pollen-pistil interactions are the prerequisite and guarantee of subsequent fertilization and seed production. Recent profile analyses have helped elucidate molecular mechanisms underlying these processes at both transcriptomic and proteomic levels, but the involvement of miRNAs in pollen-pistil interactions is still speculative. In this study, we sequenced four small RNA libraries derived from mature pollen, in vitro germinated pollen, mature silks, and pollinated silks of maize (Zea mays L.). We identified 161 known miRNAs belonging to 27 families and 82 novel miRNAs. Of these, 40 conserved and 16 novel miRNAs showed different expression levels between mature and germinated pollen, and 30 conserved and eight novel miRNAs were differentially expressed between mature and pollinated silks. As candidates for factors associated with pollen-silk (pistil) interactions, expression patterns of the two sets of differentially expressed miRNAs were confirmed by stem-loop real-time RT-PCR. Transcript levels of 22 predicted target genes were also validated using real-time RT-PCR; most of these exhibited expression patterns contrasting with those of their corresponding miRNAs. In addition, GO analysis of target genes of differentially expressed miRNAs revealed that functional categories related to auxin signal transduction and gene expression regulation were overrepresented. These results suggest that miRNA-mediated auxin signal transduction and transcriptional regulation have roles in pollen-silk interactions. The results of our study provide novel information for understanding miRNA regulatory roles in pollen-pistil interactions.